Why WSDM matters the role of WSDM in distributed IT management. - Peltz, Chris
The world of IT management has changed a great deal since the early days of SNMP and network management. IT organizations today are building and deploying a wide range of systems and applications that must be managed in a consistent and reliable way. Applications are being built from the ground up using service-oriented design principles and an IT manager can no longer look to a single machine to determine the health and availability of the services being delivered. Resources are much more distributed and interconnected and they are being deployed at an alarming rate. For IT, this poses additional challenges in having to keep track of changes and to build management solutions that can aid in linking business needs to IT.